Istilah undang-undang : English-Malay, Malay-English, Arabic-English - Jaques, Rachel (Petaling Jaya : Sweet & Maxwell Asia, 2008)
English-Malay, Malay-English, and Arabic-English dictionary of legal terms
English, Malay, and Arabic
Keywords: Law -- Dictionaries; English language -- Dictionaries -- Malay; Malay language -- Dictionaries -- English; Arabic language -- Dictionaries -- English